Purchase Intention of Green Beauty Product: Does Perceived Value Matter? - Dewi, Cynthia Sari; Windarko, Windarko; Lastro, Djano; Alam, Hanifah Pagar; Felicia, Felicia (Dinasti Publisher, 2025)
The increasing environmental impact of the cosmetics industry has led to a growing consumer interest in eco-friendly products. This study examines the purchase intentions of Indonesian millennials for green beauty products, focusing on the role of perceived values, which are functional, social, and emotional. Using a quantitative approach, data were collected from 190 millennials through an online survey and analyzed using SPSS 24. The results reveal that functional value, social value, and emotional value positively and significantly influence purchase intention. These findings underscore the importance of emphasizing product functionality, social contributions, and emotional engagement in marketing strategies. This research provides valuable insights for businesses seeking to align with sustainability goals and cater to environmentally conscious consumers. Future studies are encouraged to explore additional factors influencing green purchase behavior across diverse demographics and regions.